The reconstruction of physical education teachers: A critical discourse analysis of regulative texts - Lise Porsanger (Cappelen Damm Akademisk NOASP, 2020)
In 2008, the Norwegian Directorate for Education and Training implemented a new circular with directives for water activities in schools and with a call for testing teachers' water competence. This circular seems to align with international school safety policies, where additional regulations and safety guidelines are put into practice in school programs such as physical education. Despite this, studies that have applied a critical discourse perspective on regulative texts in physical education seem scarce. The purpose of this article is to examine how teachers' risk and safety management in physical education is constructed in five regulative documents governing primary and secondary schools in Norway. Norman Fairclough's critical discourse methodology has been applied to conduct a linguistic and contextual analysis of language. The analysis seems to reveal a discourse that challenge teachers' autonomy and position. Because the discourse can appear to be neutral and imperative, it might be taken for granted in the field. The entrancement of a controller in examining teachers' water competence seems to reflect ideals of revision and central control. This article therefore contributes to the understanding of regulative discourses and their power, in education and physical education.